Responsibility to Customers in the Context of Public Value Management – a German Case Study - Markus Bodemann; Marieta Olaru (Amfiteatru Economic)
This paper provides results obtained within a questionnaire-based survey conducted in small to medium public administrations in Germany. The survey was carried out on the occasion of working out indicators of risks and application of risk management for public sector. The results of the questionnaire enlighten reasons for undesired deviations from plans and strategy; in addition self-estimation of internal or external factors of decisions under not-certainty and their ramifications to the sustainable execution of obligatory and voluntary tasks. Hence the results are helpful to enlighten customer responsibility. This field research was carried out in the period 2009-2012 with data evaluated from 23 filled in questionnaires with 45 questions. Targets were small to middle local municipalities up to 100.000 inhabitants and county administrations up to 400.000 inhabitants in North Rhine Westphalia of prime importance. The public administrations are forced by law to introduce the accrual accounting system, similar to private sector. Financial statements lead to a similar interpretation. Addressed were mayors and treasurers. The research is replenished by borrowings by Van der Wal, et al., 2008 and Bogumil, et al., 2007. Virtual safety of existence and financing of public administrations have influence to the quality and quantity of public provided services and goods. The results of handling uncertainty, isolated projects and political decisions confirmed a peculiar dealing with accountability, responsibility and finances. Recognizing the steady convergence of operations and strategy of public and private sector organization considering leadership, processes or budgets, a peculiar kind of responsibility to the customers is confirmed, but also an endeavor to use the system for personal interests and protection instead to regard themselves as service provider for individual and collective utility, enhancing public value as objective to be legal pursuit by governmental programs.